Analisis Penggunaan Platform E-commerce pada Masyarakat di Desa Lalonggombu, Kecamatan Lainea, Kabupaten Konawe Selatan - Murniati Murniati; Murni Nia; Muhammad Juwantho Lewa; Juli Regina (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the use of e-commerce platforms among the community in Lalonggombu Village, Lainea District, Konawe Selatan Regency. This study employs a qualitative approach with a descriptive method to explore the phenomenon of e-commerce usage in everyday life. Data were collected through interviews, observations, and documentation involving community members who use e-commerce platforms. The results indicate that the use of e-commerce platforms in Lalonggombu Village has increased along with the development of digital technology. The community utilizes e commerce due to its ease of access, time efficiency, and the availability of various promotional features such as discounts, cashback, and free shipping. The use of e-commerce is characterized by high frequency of access, relatively long usage duration, and increasing transaction intensity.  However, the convenience of e-commerce usage also reflects a shift in consumption patterns from need-based consumption to desire-oriented consumption. This is indicated by unplanned purchases and intensive use of promotional features that encourage higher consumption activities.  In conclusion, the use of e-commerce platforms has become an integral part of the community’s daily life in Lalonggombu Village and has the potential to influence consumption patterns. Therefore, awareness is needed to ensure that e-commerce is used wisely and consumption remains rational and based on actual needs.